A direct catalytic aldol route to protected beta-hydroxy-alpha-amino acids - Willis, M; Piccio, V (2002)
The combination of triethylamine, magnesium(II) perchlorate and bipyridine generates a catalyst system for the efficient combination of ethyl isothiocyanatoacetate and a range of aromatic aldehydes. The products of these reactions are synthetically valuable protected β-hydroxy α-amino acids.